Chinese Parent Intention to Vaccinate Children With Special Diseases Against COVID-19 - Wang, Xu; Yan, Wu; Lu, Lingling; Cao, Liming; Tian, Ye; Zhou, Kai (Frontiers in Public Health, 2021)
Background: Information on the intention of parents of children with special diseases to vaccinate their children against coronavirus disease 2019 (COVID-19) is scarce. Methods: In this survey, all participants (n = 914) were enrolled from a tertiary children's hospital between September 2020 and April 2021. A face-to-face questionnaire interview was conducted to collect information on the special diseases of children and parental attitudes about the COVID-19 vaccine. We compared the demographic and disease factors between the group of parents who were willing to vaccinate their children against COVID-19 and the group who were unwilling to vaccinate. Results: Among 941 children, 58.1% (n = 547) were boys. The Mean age was 1.4 (SD 1.9) years. If the COVID-19 vaccine becomes available for the child, 470 (49.9%) of parents were willing to provide vaccination for their children. The less the education levels of the father or mother, the more likely they were to vaccinate their children (P = 0.003, P = 0.007). However, more intentions to vaccinate were provided in parents of children with COVID-19 prevention and control education (P < 0.001). Conclusion: Our findings provided evidence that some parents are willing to vaccinate their children with special diseases against COVID-19. Professional knowledge about COVID-19 prevention and control may contribute to increased parental intention.